Hubungan Supervisi dengan Pelaksanaan Komunikasi Efektif Perawat di Rumah Sakit Islam Sultan Agung Semarang - Amelia Hidayati; Muh. Abdurrouf; Dyah Wiji Puspita Sari (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Background: Effective communication is an importat component in improving patient safety in hospitals. Ineffective communication can lead to misperceptions, errors in treatment, and an increased risk of medication errors. Therefore, supervision is necessary to ensure that nurses’ communication meets standards. This study aims to determine the relationship between supervision and the implementation of effective communication by nurses at Sultan Agung Islamic Hospital in Semarang. Method: This study used an analytical quantitative design with a cross-sectional approach. The study sample consisted of 94 nurse practitioners, selected using total sampling technique. The reearch instruments were a supervision questionnire and an obervation sheet on effective communication based on the SBAR method. Data analysis used Pearson product moment rank correlation test to determine the relationship between the two variables. Results: The results show that most nurses have effective communication in the “fair” category, with 70 respondents (74,5%), and supervision in the “moderate” category, with 75 respondents (79,8%). The Pearson product moment test obtained a p-value of 0.025 (< 0.05), which means hat there is a relationship, and r = 0.232, which indicates a weak relationship, and r = 0.232, which indicates a weak relationship and a positive direction. Conclusion: There is a Relationship Between supervision and the implementation of effective communication by nurses